Assessment of Hearing or Vision Impairment in Studies Collecting Cognitive Data in Older Adults. (16th December 2020) - Liu, Chelsea; Assi, Lama; Nagarajan, Niranjani; Powell, Danielle; Jiang, Kening; Villavisanis, Dillan; Swenor, Bonnielin; Deal, Jennifer
Abstract: Despite the high prevalence of sensory impairment in older adults, there are no standard practices for its consideration in cognitive studies. We conducted a systematic review to identify and survey prospective cohort studies collecting cognitive data in older adults in order to determine whether and how hearing and vision were considered. Among 81 cohorts that responded, 30 (37%) objectively assessed hearing, with audiometry as the most frequently-used method; 61 (75%) used patient-report and 12 (15%) used provider-report to subjectively assess hearing. Forty-one (51%) cohorts objectively assessed vision, half of which measured distance or near visual acuity; 55 (68%) used patient-report and 10 (12%) used provider-report to subjectively assess vision. Nineteen (23%) cohorts offered hearing accommodations and 30 (37%) offered vision accommodations during cognitive testing. Findings indicate variation in methods used to assess hearing and vision as well as in accommodation practices that could impact estimates of cognition among older adults.